(untitled) (Research, Society and Development, 2020)
Objective: To draw a parallel between the neurological model developed by Freud in 1895 and his metapsychological constructs of 1900 and 1923. Methods: This is a literature review based on the following writings by Freud: “Project for a scientific psychology” (1895), “The interpretation of dreams” (1900) and “The I and the id” (1923). Other works and other authors were also included. Literature review: It made it possible to identify that, in order to continue his theory of mind, Freud migrated from the neurological model to a virtual perspective of psychic activity. In this process, Freud went through three models - the neurological model (1895), the topographical model (1900) and the structural model (1923). Conclusion: It is concluded that the ideas and concepts developed in the 1895 neurological model are present throughout the evolution of Freud’s theoretical constructs.